MO268GLOMERULAR C3 DEPOSITS IN ANCA ASSOCIATED PATIENTS – IS IT AN IMPORTANT FINDING?. (29th May 2021) - Crnogorac, Matija; Horvatić, Ivica; Kacinari, Patricia; Tišljar, Miroslav; Brechelmacher, Ana; Senjug, Petar; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: Background and Aims: In recent years there were many studies explaining the role of alternative complement pathway (aCP) in etiopathogenesis of the ANCA associated vasculitis (AAV) and weather it affects patient outcomes. We hypothesized the importance of the C3 positive staining in glomeruli and that there could be differences between clinical, serological and histological phenotypes in AAV patients. Method: This study included 106 consecutive AAV patients with renal involvement in the period from 2007-2017. We performed renal biopsy on patients using automatic 16 Gauge needle. Light, immunofluorescent and electronic microscopy were performed. Category variables were analysed with Fisher Exact testom and continuous with Kruskal-Wallis testom. Statistical difference was then analysed posthoc with Chi-square test. Primary outcomes were combined outcome progression to end-stage renal disease, defined as persistent (more than three months) need for renal replacement therapy or permanent reduction of EGFR to <15ml/minute (according to CKD EPI formula) and/or death (ESRDD), death (D) and ESRD alone, and disease relapse. Kaplan Meyer survival analysis and multivariate Cox proportional hazard regression analysis were used to explore difference between phenotypes and finding significant predictors regarding outcomes. Results: The study included 106 AAV patients with renal involvement: 66 (61, 1%) MPA, 20 (18, 5%) GPA, 20 (18, 5%) RLV. There were 14 (13%) PR3-ANCA positive patients, 57 (52, 8%) MPO ANCA positive, 5 (4, 6%) PR3-ANCA+MPO-ANCA and 32 (29, 6%) ANCA negative patients. Average SCr was 316, 5 μmol/l (IQR 207, 0-548, 5), 24-hour proteinuria median was 1, 7g/24h (IQR 0, 8-2, 8). Histologicaly (Berden classification) 43 (39, 8%) patients had crescentic, 19 (17, 6%) focal, 34 (31, 5%) mixed and 12 (11, 1%) sclerotic class. Out of all, 48, 5% MPA patients had C3 deposits in glomeruli compared to 25% GPA and 35% RLV though statistical significance was not reached (p=0, 1). Same applied for serological phenotypes: MPO-ANCA and ANCA negatives had more C3 deposits but statistical significance was not reached (p=0, 6). When comparing histopathological classes there was strong tendency of crescentic class having more C3 deposits (p=0, 076) compared to focal and mixed. In sclerotic class 50% had C3 deposits but C3 deposits can be ordinary found in sclerotic lesions so the interpretation is more challenging. Interestingly patients requiring haemodialysis had strong tendency of having more C3 deposits compared to those not needing haemodialysis treatment (p=0, 09). Conclusion: Glomerular C3 deposits in kidney tissue samples could prove to be a useful tool for perhaps predicting the severity and the course of the disease. Though differences between various groups in our cohort didn't have statistical significance, there was a tendency for MPA patients, those with MPO-ANCA and those with crescentic class of having higher proportion of C3 deposits in glomeruli compared to other groups. This could suggest more aCP activation in MPO positive AAV. Also there was strong tendency of patients requiring dialysis having higher proportion of C3 deposits compared to non-dialysis patients which could signify C3 deposition of being the hallmark of more severe renal involvement in AAV patients. This data needs further confirmation from future studies.